Selecting and implementing an integrated library system : the most important decision you will ever make - Jost, Richard (Waltham, MA : Chandos Publishing, an imprint of Elsevier, 2016)
Selecting and Implementing an Integrated Library System: The Most Important Decision You Will Ever Make focuses on the intersection of technology and management in the library information world. As information professionals, many librarians will be involved in automation projects and the management of technological changes that are necessary to best meet patron and organizational needs. As professionals, they will need to develop numerous skills, both technological and managerial, to successfully meet these challenges. This book provides a foundation for this skillset that will develop and acquaint the reader with a broad understanding of the issues involved in library technology systems. Although a major topic of the book is integrated library systems (a fundamental cornerstone of most library technology), the book also explores new library technologies (such as open source systems) that are an increasingly important component in the library technology world. Users will find a resource that is geared to the thinking and planning processes for library technology that emphasizes the development of good project management skills.
Brief history of library technology -- Record types and print library workflows -- Electronic resources -- Systems librarians -- Project management -- Change management -- Needs assessment and the library automation marketplace -- Open source -- Decision trees and consultants -- Request for proposal -- Data migration, retrospective conversion, and barcodes -- Staff training and troubleshooting -- Staffing the libraries of the future -- Library transformation in the digital age -- Conclusion -- Appendix: The Orbis-Cascade project.
Includes bibliographical references (page 105) and index.
Print version record.
Keywords: Integrated library systems (Computer systems); Libraries -- Automation; Integrated library systems (Computer systems); Libraries -- Automation; Electronic books; Electronic books